Vosoritide (Voxzogo) - CDA-AMC (Canadian Journal of Health Technologies, 2026)
Canada’s Drug Agency (CDA-AMC) recommends that Voxzogo not be reimbursed by public drug plans for increasing linear growth in patients with achondroplasia (ACH) who are 4 months of age and older whose epiphyses are not closed. The Canadian Drug Expert Committee (CDEC) concluded that it is uncertain whether Voxzogo demonstrates acceptable clinical value compared with best supportive care alone in patients 4 months of age and older with ACH whose epiphyses are not closed. Given that Voxzogo is expected to be an added treatment to best supportive care, acceptable clinical value refers to added value versus best supportive care alone. Evidence from 2 double-blind, randomized controlled trials (RCTs) showed that Voxzogo increased annualized growth velocity in patients younger than 18 years, and increased height z scores in patients aged 5 years to younger than 18 years compared with placebo at 52 weeks. However, there was little to no demonstrated benefit in patient-important outcomes at 52 weeks, including body proportionality, health-related quality of life, or sleep apnea, and the clinical significance of the observed height gains for improving patient-important outcomes remains uncertain. Long-term extension studies suggested sustained effects on height, but interpretation was limited by the lack of a comparator group. Overall, it remains uncertain whether Voxzogo improves long-term functional outcomes, ACH-related complications, and the need for surgery or supportive care. CDEC further reviewed evidence from 6 sponsor-submitted studies, including the Natural History Integrated Comparative Analysis, 3 real‑world evidence studies, and 2 additional analyses of the 2 double-blind RCTs that intend to address gaps in the evidence. However, due to important methodological limitations of the studies, CDEC was unable to draw conclusions on the comparative effects of Voxzogo. CDEC concluded that the results from these studies did not meaningfully address the key evidence gap remaining from the 2 RCTs and their long-term extension studies, which is the absence of comparative evidence versus placebo beyond 52 weeks. The submitted studies primarily provided additional evidence on growth outcomes but evidence for the long-term outcomes identified as important by patients and clinicians was either uncertain or unavailable. CDEC considered there to be significant unmet need based on potential challenges with evidence generation associated with the rarity of ACH and the severity of ACH despite available treatment options. However, even when taking the significant unmet clinical need into account, CDEC was unable to conclude that Voxzogo addresses the unmet need with an acceptable level of certainty in clinical value. CDEC acknowledged that there is a significant unmet nonclinical need given that current supportive treatments are mainly available in tertiary pediatric care centres. This can create barriers to accessing care for patients living in rural areas or for those with fewer resources who may face travel-related burdens. However, CDEC was unable to conclude that Voxzogo addresses this significant unmet nonclinical need and health inequity because the submitted evidence did not demonstrate that Voxzogo could reduce the need for specialized services or supportive treatments. Based on all the preceding considerations, CDEC recommended that Voxzogo not be reimbursed.